Challenges, Changes and Constraint: Transforming the Response ofthe Canadian State to Wife/Woman Abuse. - Preston, Sandra (My University, 2000)
This work explores the process of social change through an examination of the interaction between the Canadian state and the women's movement at the macro, mezzo and micro level concerning the issue of woman abuse. Using an expanding case study, an analysis of a small family service agency, a medium size Canadian city and the parliamentary and public hearing process are combined to examine how feminist challenges at various levels have interacted to transform the response of the state to woman abuse.
In addition, this work examines the effectiveness of various feminist approaches to creating change. I challenge the dichotomy between mainstreaming and disengagement (Adamson et al ,1988) arguing that when it comes to effective action it is not a question of 'either/or' but rather 'which one, when'. The conclusion of the work is that challenge is required from many locations, in many different forms if change is to occur.
Keywords: woman abuse; challenges; response; wife; Family, Life Course, and Society; Gender and Sexuality; Inequality and Stratification; Sociology; Family, Life Course, and Society